Eating Habits and Anthropometric Characteristics Among Individuals with Type 2 Diabetes Mellitus A review - Suheir Abdul Mohsen Al-Gaedan et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Type 2 Diabetes Mellitus (T2DM) is a global epidemic intrinsically linked to modifiable lifestyle factors. Eating habits and specific anthropometric profiles are central to both the etiology and management of the disease. Understanding their interrelationship is crucial for effective prevention and treatment strategies. This narrative review synthesizes current evidence on the distinctive eating patterns and anthropometric characteristics observed in individuals with T2DM, exploring their bidirectional relationship and clinical implications. A synthesis of contemporary literature and key guidelines from sources such as the American Diabetes Association (ADA), World Health Organization (WHO), and peer-reviewed journals was conducted, focusing on reviews and meta-analyses from the past decade. Key Findings: Individuals with T2DM consistently exhibit anthropometric profiles marked by central adiposity, reflected in elevated waist circumference and high waist-to-hip ratios, even when BMI falls within the normal range. Eating habits are frequently characterized by high intake of refined carbohydrates, added sugars, and saturated fats, alongside low fiber consumption. Mediterranean and DASH dietary patterns are associated with improved glycemic control and favorable anthropometric changes. A strong bidirectional relationship exists where poor dietary choices drive adverse changes in body composition (particularly increased visceral fat), which in turn exacerbates insulin resistance and influences dietary behaviors and energy metabolism. The synergy between dysregulated eating habits and adverse anthropometry forms a core pathophysiological axis in T2DM. Effective management necessitates integrated interventions that simultaneously target diet quality and body composition, with a particular emphasis on reducing central obesity. Future research should prioritize personalized nutrition approaches based on individual anthropometric and metabolic phenotypes. Keywords: Type 2 Diabetes, Eating Habits, Dietary Patterns, Anthropometry, Waist Circumference, Obesity, Insulin Resistance. Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/539